On the diffusive water transport through polyelectrolyte-based membranes - Jannik Mehlis; Matthias Wessling (Journal of Membrane Science Letters)
This study investigates water transport behavior through polyelectrolyte membranes under varying pressure gradients using non-equilibrium molecular dynamics (NEMD) simulations. While net water transport is achieved under a pressure gradient, there is also a significant back-diffusion component, challenging the assumption of unidirectional pore flow in such systems. The auto-correlation function of water molecules reveals that water associations are transient and only occur for short periods compared to the overall residence time within the membrane. The correlation of water associations and the water dynamics inside the membrane are not affected by varying pressure differences, which also favors the assumption of a diffusive transport mechanism rather than pore flow. Furthermore, our NEMD simulations provide a detailed analysis of the diffusion-related time lag, revealing an initial transient water transport response and a constant diffusive time lag for all pressure differences. These findings enhance our understanding of water transport mechanisms in membrane systems, underlining the validity of the solution-diffusion model for dense polymeric membranes. The methodology described can be applied to shed light on the discrimination between pore flow and solution-diffusion phenomena.